Implementation of village road infrastructure development policy using Van Meter and Van Horn models - Muksin, Zainal; Rahim, Abdur; Hermansyah, Andi; Andriansyah; Satispi, Evi (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2024)
The researcher wants to know how far the implementation of policies in the field of road construction has been carried out by the local government and various parties involved in road construction in villages using the Van Meter and Van Horn models which are based on six variables, namely: 1). Policy standards and targets/measurements and policy objectives, 2). Resources, 3). Characteristics of implementing organizations, 4). Attitude of executors, 5). Communication between related organizations and implementation activities, 6). Social, economic and political environment. This type of research is a type of qualitative descriptive research using data collection methods through observation, interviews. Results. This research can be seen from the six variables in the Van Mater and Van Horn models on the implementation of road infrastructure development policies in subdistricts, namely the implementation of the policy has been successful. From the results of this study it is known that through the Van Mater and Van Horn models the implementation of road infrastructure development policies in sub-district has been successful. The construction of a 9.3 Km road connecting the village is almost complete. It would be nice if the construction continues until all existing access roads are good.